Comparative Proteomics of Whey and Milk Fat Globule Membrane Proteins of Guanzhong Goat and Holstein Cow Mature Milk. Issue 2 (8th January 2019) - Sun, Yuxue; Wang, Cuina; Sun, Xiaomeng; Guo, Mingruo
Abstract : Abstract: Guanzhong goat and Holstein cow milks are the major milk supply for the Chinese dairy industry. Whey proteins and milk fat globule membrane (MFGM) proteins of both milk were characterized and compared using proteomic techniques. A total of 283, 159, 593, and 349 proteins were identified, respectively, in whey and MFGM for the two species using Liquid Chromatography combined with Tandem Mass Spectrometry (LC‐MS/MS). Functional categories analyses showed that both goat and cow MFGM proteins had three most abundant proteins of phosphoproteins, membrane‐related and acetylation‐related proteins. Gene ontology (GO) annotation revealed that whey proteins in goat and cow milk exhibited different biological processes and molecular functions while both enriched in extracellular exosome for cellular components. Both goat and cow MFGM proteins showed main biological process of oxidation‐reduction, cellular component of extracellular exosome, and molecular function of poly(A) RNA binding. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses showed that large number of both goat and cow whey proteins were involved in disease, metabolism, and immune pathways with different number and types. The most general pathways for goat and cow MFGM proteins were metabolism pathways and disease pathways, respectively. The results indicated that Guanzhong goat and Holstein cow milk were different in varieties of whey proteins and MFGM proteins and their functions and pathways. Practical Application: Guanzhong goat and Holstein cow milks are the major milk sources for the Chinese consumers. However, information about proteomics of whey and MFGM proteins of Guanzhong goat and Holstein cow milk is limited. Our study characterized and compared both whey and MFGM proteins using proteomic techniques. The results provide useful information for infant formula and milk protein products in the Chinese dairy industry.